2021
DOI: 10.3389/fpsyt.2021.596281
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Implementation of Statutory Preventative Measures, Perceived Susceptibility of COVID-19, and Personality Traits in the Initial Stage of Corona-Related Lockdown: A German and Austrian Population Online Survey

Abstract: Background: Particularly during the early and middle stages of the COVID-19 pandemic, a population's compliance with precautionary measures (e.g., hygiene rules, smart working, travel restrictions, and quarantine) is paramount in preventing the virus from spreading.Objective: The investigation and documentation of different socio-demographic and personality-specific factors in regards to preventative measures and consequent specific health behaviors during the COVID-19 pandemic, based on the Health Belief Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 48 publications
0
21
0
2
Order By: Relevance
“…These measures were aimed at reducing the spread of the virus through person-to-person contact. The COVID-19 pandemic led governments and responsible parties, as well as mass communication and the press to communicate these behaviors in many countries, including Germany [5,6] and to ensure patient safety. Accordingly, it was often found that the level of fear, worry or concern of own risk of SARS-CoV-2 infection was interrelated with the prevalence of frequent hand hygiene [7,8] but not with physical distancing, leaving home for food or to exercise [7].…”
Section: Introductionmentioning
confidence: 99%
“…These measures were aimed at reducing the spread of the virus through person-to-person contact. The COVID-19 pandemic led governments and responsible parties, as well as mass communication and the press to communicate these behaviors in many countries, including Germany [5,6] and to ensure patient safety. Accordingly, it was often found that the level of fear, worry or concern of own risk of SARS-CoV-2 infection was interrelated with the prevalence of frequent hand hygiene [7,8] but not with physical distancing, leaving home for food or to exercise [7].…”
Section: Introductionmentioning
confidence: 99%
“…As China recovered from the pandemic after the lockdown was lifted, only 13.0% of our participants considered that they had a high risk of being infected. Their reduced self-perceived risk of COVID-19 infection might lead to less compliance with restrictions measures (e.g., wearing masks) [ 23 ]. Given that therapeutics for COVID-19 have yet to be discovered, and the public’s adherence to restriction measures was weaken, a vaccine was needed to assure that normal life would continue and to prevent further waves of infection [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive correlation identified between COVID-19 susceptibility and extraversion highlighted by the LDSC approach appears to be in line with the literature. Numerous studies performed both before and during the SARS-CoV-2 pandemic have demonstrated the effect of personality determinants on health behaviour and outcomes (such as 5 , 34 , 35 ). For example, it was shown that narcissistic tendencies coincide with decreased perceived susceptibility to infection with SARS-CoV-2 36 whereas, at least for neuroticism, no genetic overlap was found.…”
Section: Discussionmentioning
confidence: 99%